2001
DOI: 10.1128/jcm.39.10.3541-3547.2001
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Heterogeneity between Far Eastern and Western Countries in Prevalence of the Virulence Plasmid, the SuperantigenYersinia pseudotuberculosis-Derived Mitogen, and the High-Pathogenicity Island amongYersinia pseudotuberculosisStrains

Abstract: Yersinia pseudotuberculosis produces novel superantigenic toxins designated YPMa ( Y. pseudotuberculosis -derived mitogen), YPMb, and YPMc and has a pathogenicity island termed HPI (high-pathogenicity island) and R-HPI (the right-hand part of the HPI with truncation in its left-hand part) on the chromosome. Analysis of the distribution of these virulence factors allowed for differentiation of species Y. pseudotuberculosis into six subgroups, thus refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
139
0
10

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 45 publications
5
139
0
10
Order By: Relevance
“…The present results also confirm the interdependence between virulence markers located on the pYV plasmid and on the chromosome for the full expression of Y. pseudotuberculosis disease, as previously reported by Carniel (2001) and Fukushima et al (2001).…”
Section: Discussionsupporting
confidence: 78%
“…The present results also confirm the interdependence between virulence markers located on the pYV plasmid and on the chromosome for the full expression of Y. pseudotuberculosis disease, as previously reported by Carniel (2001) and Fukushima et al (2001).…”
Section: Discussionsupporting
confidence: 78%
“…In a previous in vivo infection kinetics study, these two samples exhibited higher pathogenicity since they were more virulent and invasive than biotype 2 and serogroup O:3 strains (Martins & Falcão 2004). Fukushima et al (2001), studying 2235 Y. pseudotuberculosis strains of various bioserotypes and origins isolated from different regions of the planet, showed that all strains of the O:1a serotype exhibited a complete HPI.…”
Section: Discussionmentioning
confidence: 99%
“…Table II shows the primers used for the detection of the HPI genes and the size (in base pairs = bp) of the expected product. Y. pseudotuberculosis PB1 (serotype O1a) (Fukushima et al 2001) was used as positive control. Reactions without DNA as template were used as negative controls.…”
Section: Determination Of Virulence Markers and Of The Is100mentioning
confidence: 99%
“…It has been shown that virulent Y. pseudotuberculosis can cause immunosuppression in laboratory mice (Simonet and Berche, 1986;Sing et al, 2002). Yersinia pseudotuberculosis is widely distributed in cold regions, and is classified as serotypes O1 to O14, in which the serotypes O1 to O5 are almost all pathogenic to humans (Fukoshima et al, 2001). The bacteria can infect many mammals and birds, with formation of characteristic caseonecrotic foci and pyogranulomatous lesions in viscera and lymphoid tissue (Valli, 1985).…”
Section: Discussionmentioning
confidence: 99%